Improving Ecological Intelligence Through Environmental Education in Elementary School Students of Indonesian Nature School - Ramdani, Gumilar; Aisy, Aisyatunnadiya (Lia Center of Research and Education, 2025)
This study investigates the role of environmental education in enhancing ecological intelligence among students at Sekolah Alam Indonesia Elementary School. Using a qualitative survey design, participants were selected through purposive sampling, including the principal, vice principal, and teachers as key informants. Data were collected through semi-structured interviews, observations, and document analyses, with instruments developed based on environmental education theories and best practices. Instrument validation involved expert assessments and pilot testing, achieving a high reliability index of 0.85 (Cronbach's Alpha). The findings indicate that initiatives to boost environmental awareness were particularly effective when applied through the Seven Green Principles in daily activities. Students showed increased awareness of actions such as reducing carbon emissions and participating in conservation efforts. The study concludes that fostering understanding of the Seven Green Principles through education on waste management, carbon reduction, organic farming, green space optimization, and renewable energy significantly enhances students' ecological intelligence. Engaging students in hands-on activities, such as establishing waste banks and exploring local ecosystems, further promotes environmental stewardship. Overall, environmental education has proven to positively influence students' ecological behaviors, such as cycling to school and participating in conservation campaigns.